Investment Policy in a Nationalised Industry - Scott, M. F. (Review of Economic Studies, 1949)
Journal Article Investment Policy in a Nationalised Industry Get access M. F. Scott M. F. Scott Oxford and Paris Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 17, Issue 3, 1949, Pages 179–188, https://doi.org/10.2307/2296277 Published: 01 January 1949